KORELASI AKTIVITAS PESERTA DIDIK BIMBINGAN KELOMPOK DENGAN INTERAKSI SOSIAL X SMA NEGERI 3 PONTIANAK - Lusia Tri Adveni; Sri Lestari; Purwanti Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
Abstrak The problem in this research is "How Correlation Between Student Activities in Group Guidance with Social Interaction class X SMA Negeri 3 Pontianak?". This study aims to determine whether there is a relationship between Student Activity in Group Guidance with Social Interaction in class X SMA Negeri 3 Pontianak. The method used is descriptive method with quantitative approach that is the problem-solving procedure by describing the relationship of Student Activity in Group Guidance with Social Interaction in class X SMA Negeri 3 Pontianak by way of statistics and explained by way of Descriptive. The sample in this research is 52 students of class X SMA Negeri 3 Pontianak, Technique of data collecting in this research is indirect communication technique Data collection tool in this research is questionnaire. Based on the results of data analysis shows that the activities of students in the guidance of groups in the class X SMA Negeri 3 Pontianak reach 91.09%, the achievement is in the range very good. While social interaction in class X SMA Negeri 3 Pontianak reach 82,62% which is in very good range. The result of product moment correlation of both variables is rhitung = 0,137 which means show that there is no correlation between learners activity in group guidance with social interaction in class X SMA Negeri 3 Pontianak.Keywords: Activity of Peseta Didik, Group Guidance, Social Interaction